Pengaruh Pemberian Telur Rebus Terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri dengan Anemia di SMA Negeri 07 OKU - Sherly Dea Amanda; Kamidah Kamidah (Calory Journal Medical Laboratory Journal, 2024)
Anemia is estimated to affect half a billion women aged 15-49 years and 269 million children aged 6-59 months worldwide. The high prevalence of anemia among teenagers, if not handled properly, will continue into adulthood and will contribute greatly to maternal mortality rates, premature babies and babies with low birth weight. Meanwhile, the immediate impact of anemia in school-aged adolescents causes a lack of concentration and decreased learning achievement. An alternative solution to meet iron needs, many foods contain sources of Fe as a way to prevent and control the incidence of anemia. Eggs are one of the foods that contain Fe. Pre- experimental research with one group pretest posttest design with a population of all young women who experienced signs of anemia at SMA Negeri 07, sample 20. Statistical tests used the Paried Sample t-test. There was an increase in Hb levels in adolescent girls by 1.47gr/dl. The results of the paired t-test obtained a p value = value 0.000 (p <0.05). There is an effect of giving boiled eggs on increasing hemoglobin levels in young women at SMA Negeri 07 OKU